2019
DOI: 10.3390/nu11030553
|View full text |Cite|
|
Sign up to set email alerts
|

Dianthus superbus Improves Glomerular Fibrosis and Renal Dysfunction in Diabetic Nephropathy Model

Abstract: Glomerular fibrosis is caused by an accumulation of intercellular spaces containing mesangial matrix proteins through either diffused or nodular changes. Dianthus superbus has been used in traditional medicine as a diuretic, a contraceptive, and an anti-inflammatory agent. The aim of this study was to investigate the effects of Dianthus superbus-EtOAc soluble fraction (DS-EA) on glomerular fibrosis and renal dysfunction, which has been implicated in diabetic nephropathy in human renal mesangial cells and db/db… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 45 publications
(39 reference statements)
0
19
0
Order By: Relevance
“…The results of the present study suggested that fibronectin, ColIV, and CTGF may be involved in the ECM-synthesizing process, and that their AngII-induced protein and mRNA expression were decreased following treatment with sauchinone. We recently reported that HG or AngII induces mesangial cell fibrosis by activation of TGF-β/Smad signaling [ 39 ]. We have now shown that sauchinone inhibited the elevated expression of TGF-β and Smad2/3 phosphorylation under AngII conditions.…”
Section: Discussionmentioning
confidence: 99%
“…The results of the present study suggested that fibronectin, ColIV, and CTGF may be involved in the ECM-synthesizing process, and that their AngII-induced protein and mRNA expression were decreased following treatment with sauchinone. We recently reported that HG or AngII induces mesangial cell fibrosis by activation of TGF-β/Smad signaling [ 39 ]. We have now shown that sauchinone inhibited the elevated expression of TGF-β and Smad2/3 phosphorylation under AngII conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Dianthus plumarius L. is an important environmental protection and greening plant, because of its strong reproductive capacity and rapid growth speed which can effectively prevent soil erosion and soil erosion [4][5][6]. Dianthus chinensis L. and Dianthus Superbus L. are used as herbal medicine for its function of reducing fever and diuresis, and also as insecticidal pesticides [7][8][9]. Dianthus barbatus L. is also an important source of cut flowers and a greening plant.…”
Section: Introductionmentioning
confidence: 99%
“…In its classic definition DN is defined as increased protein excretion in urine [8]. Major representations of diabetes in renal disease include persistent albuminuria, loss of podocytes, glomerular hypertrophy, matrix expansion, and thickening of the glomerular basement membrane [9,10]. The first stages of DN are characterized by microalbuminuria, a small increase in albumin excretion in urine [11,12,13].…”
Section: Introductionmentioning
confidence: 99%